2017
DOI: 10.1115/1.4035511
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Crystalline Nanowires: An Experimental Perspective

Abstract: A wide variety of crystalline nanowires (NWs) with outstanding mechanical properties have recently emerged. Measuring their mechanical properties and understanding their deformation mechanisms are of important relevance to many of their device applications. On the other hand, such crystalline NWs can provide an unprecedented platform for probing mechanics at the nanoscale. While challenging, the field of experimental mechanics of crystalline nanowires has emerged and seen exciting progress in the past decade. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 323 publications
(560 reference statements)
0
21
1
1
Order By: Relevance
“…Different from bulk materials, surface dislocation nucleation has been identified as a dominant deformation mechanism in NWs. Extensive research has been performed on defect-free, single-crystalline metallic NWs where surface-nucleated dislocations tend to slip across the NW, as a result of two competitive deformation mechanisms, twinning and localized dislocation slip. , The former leads to large plasticity, while the latter results in limited plasticity. Thus, it is of interest to study how the two deformation mechanisms compete with each other in face-centered cubic (FCC) metallic NWs and what the underlying factors are.…”
mentioning
confidence: 99%
“…Different from bulk materials, surface dislocation nucleation has been identified as a dominant deformation mechanism in NWs. Extensive research has been performed on defect-free, single-crystalline metallic NWs where surface-nucleated dislocations tend to slip across the NW, as a result of two competitive deformation mechanisms, twinning and localized dislocation slip. , The former leads to large plasticity, while the latter results in limited plasticity. Thus, it is of interest to study how the two deformation mechanisms compete with each other in face-centered cubic (FCC) metallic NWs and what the underlying factors are.…”
mentioning
confidence: 99%
“…Dislocation nucleation from free surfaces has been identified as a dominant deformation mechanism in NWs, in contrast to the forest dislocation dynamics in bulk materials. Extensive studies have been reported for defect-free, single crystalline metallic NWs where surface dislocation nucleation is dominant [5][6][7][8][9][10][11][12][13][14][15][16]. Such NWs exhibit ultrahigh yield strength [17,18], but typically with limited or no strain hardening and low tensile ductility due to the absence of effective obstacles within the NWs that could block the movement of dislocations.…”
mentioning
confidence: 99%
“…Over the past years, many researchers have worked on theoretical models to describe the size effects in the elastic behavior of nanowires. The sizedependent change in elasticity has been attributed to one or more of the following factors: Loss of atomic coordination [30], electron density redistribution [31], lattice contraction due to compressive strain [32], surface relaxation processes [33], and facet energy [34]. He and Lilley presented a theoretical approach analyzing the influence of surface stress on static bending [35] and in resonance vibration [36].…”
Section: Discussionmentioning
confidence: 99%